Implementasi Kebijakan Penyuluh KB pada Dinas Pengendalian Penduduk Dan Keluarga Berencana (DPPKB) di Kabupaten Minahasa - Ante, Lady Deiby; Bogar, Wilson; Mamonto, Fitri H. (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This study This study aims to determine 1) the ratio of family planning instructors to the number of assisted villages/sub-districts in the implementation of family planning programs in the field in terms of placement through the Minahasa Regency Population Control and Family Planning Office; 2) The process of distributing PLKB through work transfers between those in the Department of Population Control and Family Planning in Minahasa Regency; 3) Fulfillment of facilities in the implementation of work in the field for PLKB through the provision of operational work facilities by the Department of Population Control and Family Planning of Minahasa Regency. The research method used is qualitative research. The results of the research that have been obtained and described are: 1) Policy implementation in the utilization of PLKB in the field in terms of placement through the Department of Population Control and Family Planning in Minahasa Regency seen through the ratio of extension workers to the target area is not fully appropriate, in the sense that the number of PLKB is not proportional to the area of The vast Minahasa Regency. Even though in terms of placement it is in accordance with the tiered procedure from Province to Regency, but there is discomfort from PLKB regarding the workload of the region. 2) Policy implementation in terms of PLKB work mutations in the Regency has generally been running in accordance with the tiered mechanism, but the distribution of PLKB has not been fully implemented, due to the limited number of PLKB so that it is only based on the domicile closest to the area of responsibility of the PLKB in addition to the existence of formation based adjustments 3) The implementation of policies in terms of fulfilling facilities in the implementation of work in the field for PLKB through the provision of operational work facilities by the Department of Population Control and Family Planning in Minahasa Regency has not been fully evenly distributed and in accordance with needs, this is because the procurement of work facilities does not involve program managers and PLKB so that there is an inappropriate target for work facilities